Mudança estratégica: o caso da expansão do Boticário - Campelo, Karen Barreto (2002)
The aim of this research was to detect how strategy changes took place in a successful organization. This was an unique case study focused on O BOTICÁRIO, a cosmetic and perfumery company in the state of Paraná, Brazil. Some information (from primary data) was obtained through interviewing members of the retail development department. Extra information was taken from articles about the company and interviews with members of the board of directors published in newspapers and magazines. The analysis was carried out in an explanatory-descriptive way, with a qualitative approach. The data, other than serving to characterize the company, was used for a number of purposes. They were: to introduce information about strategy changes in the company; to identify factors that gave rise to these changes; to identify the effects of these changes on the organization; to classify the strategy changes. The data revealed that the company is highly receptive to changes. Amongst the factors that caused strategy changes the following two factors stand out: the flexibility that the company presents in adapting to environmental variations and, overall, the interdependency that exists between changes. Confirming the systemic character of organizations, it was found that the changes lead to new changes. When qualifying the strategy changes, it was discovered that the incremental changes were more related to process evolution, i.e., comprehending transformations directly related to the activities to which the changes are associated with. The discontinuous changes, on the contrary, involved transformations throughout the whole company. Of all the changes that were analyzed only two were considered to be truly strategy revolutions. This confirms the idea that organizations usually choose to search for established strategic paths. The strategy changes analyzed produced a resistance level. This resistance was directly proportional to the level of discontinuance that the change had. It was verified, however, that all changes were considered beneficial to the company. The study concludes that other factors are also responsible for the fast expansion of the company. The most important of these are: the constant lauching of new products; the identification of the company with environmental issues; the policy towards employees; the strong marketing strategy; the quality of its products; the excellence on its services; the treatment of consumers; the use of franchise shops; the training provided to all the franchise network and as well as to the employees; and the seek to hire the best professionals to supervise its services. However, it can¿t be omitted that particular cause of O BOTICÁRIO¿s success is the intuition and the feeling of its President.